Redundancy relations for fault diagnosis in nonlinear uncertain systems - Shumsky, Alexey (Zielona Góra: Uniwersytet Zielonogórski)
The problem of fault detection and isolation in nonlinear uncertain systems is studied within the scope of the analytical redundancy concept. The problem solution involves checking the redundancy relations existing among measured system inputs and outputs. A novel method is proposed for constructing redundancy relations based on system models described by differential equations whose right-hand sides are polynomials.
Keywords: fault detection and isolation; nonlinear systems; redundancy relations; full decoupling; algebraic approach; geometric approach